Haploidentical donor stem cell transplantation had a lower incidence of bronchiolitis obliterans syndrome compared with HLA-matched sibling donor transplantation in patients with hematologic malignancies: Benefit from ATG? - Weng, Guangyang; Fan, Zhiping; Xue, Huiwen; Huang, Fen; Xu, Na; Jin, Hua; Yu, Sijian; Ye, Zhixin; Fan, Jingchao; Xuan, Li; Liu, Qifa (Frontiers in Immunology, 2022)
Background: Haploidentical stem cell transplantation (HID-SCT) based on antithymocyte globulin (ATG) for GVHD prophylaxis had achieved similar incidence of cGVHD with HLA-matched sibling transplantation (MSD-SCT). However, bronchiolitis obliterans syndrome (BOS) serves as pulmonary cGVDH, was rarely compared between HID and MSD transplantation. Methods: One thousand four hundred and five patients with hematologic malignancies underwent allogeneic SCT were enrolled in this retrospective study. Based on donor type, we divided the patients into three groups: HID, MSD and MUD (match unrelated donor) groups. The cumulative incidences and risk factors of BOS were analyzed. Results: The 5-year cumulative incidence of BOS was 7.2% in the whole population. HID transplantation had lower 5-year cumulative incidence of BOS than MSD transplantation (4.1% vs 10.0%; p<0.001), and the similar incidence with MUD transplantation (4.1% vs 6.2%; p=0.224). The 5-year cumulative incidence of BOS was lower in ATG group than that in non-ATG group in the whole and MSD population both (4.6% vs 11.2%; p<0.001; and 4.1% vs 11.2%; p=0.042, respectively). . The 5-year incidence of BOS in mixed grafts (peripheral blood stem cell plus bone marrow) group was also lower than that in PBSC (peripheral blood stem cell) group (4.2% vs 9.1; p=0.001). Multivariate analysis showed that HID, ATG and mixed grafts were protective factors for BOS (OR 0.3; 95%CI, 0.2 to 0.6; p<0.001; OR 0.3; 95%CI, 0.2 to 0.7; p=0.001; OR 0.3; 95%CI, 0.1 to 0.8; p=0.013), and aGVHD and cGVHD were independent risk factors for BOS (OR 2.1; 95%, 1.1 to 4.3; p= 0.035; OR 10.1; 95%CI, 4.0 to 25.0; p<0.001). Conclusions: HID transplantation had a lower incidence of BOS than MSD transplantation, which might be associated with ATG and mixed grafts.